Analyzing the Characteristics of Highly Educated Unemployment in Indonesia’s Capital City - Febrim Leksiando Sipayung; Andi Fefta Wijaya; Fadillah Putra; Natsumi Aratame (Universitas Negeri Malang, 2022)
Indonesia’s capital city, Jakarta, is facing a problem of highly educated unemployment, a phenomenon that has become a very serious issue as Indonesia's population continues to increase facing the demography dividend. This study aims to analyze the characteristics of highly educated unemployment in Jakarta, the biggest city in Indonesia. The logistic a regression model is used to analyze the labor force associated with important aspects such as highly educational attainment, age, gender, marital status, and status in the household. This study finds that being less-educated, young, male, single, and member of the household respectively increase the probability of being unemployed. However, it also finds that the total effect of highly educational attainment on the probability of employment peaks maximum value when the labor forces are single and head of the household and drops to the lowest value when the labor forces are married and member of the household.